Pengaruh Disiplin dan Motivasi Terhadap Kinerja Guru dan Pegawai (Studi Kasus MAN 3 Kota Padang Panjang) - Febrianti, Eka; Asnah; Nasfi (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2022)
The purpose of the study was to determine the effect of discipline on the performance of teachers and employees, to determine the effect of motivation on the performance of teachers and employees and to determine the effect of discipline and motivation on the performance of teachers and employees at MAN 3 Padang Panjang City. The type of research is descriptive research, using multiple regression test and using statistical tools Pragram For Social Scence (SPSS). The data used are secondary data and primary data taken at MAN 3 Padang Panjang at the end of 2021. The population is all 41 teachers and employees of MAN 3 Padang Panjang, as well as as many as samples. The variables in this study are; first, the independent variable (X) which includes Discipline (X1) and Motivation (X2), second, the dependent variable (Y) Performance at MAN 3 Padang Panjang. And measuring the variables used Sklala Linkert, as well as the results analysis method with Instrumental test, descriptive analysis of variables and classical assumption test and hypothesis testing. The results of multiple regression analysis with the results of Y=29.356+0.389X1+0.372 X2, where it was found that discipline had a significant effect on teacher and employee performance, motivation had a significant effect on teacher and employee performance and discipline and motivation together had a significant effect on performance of teachers and employees at MAN 3 Padang Panjang.